2018
DOI: 10.3390/drones2010007
|View full text |Cite
|
Sign up to set email alerts
|

UAS Navigation with SqueezePoseNet—Accuracy Boosting for Pose Regression by Data Augmentation

Abstract: Abstract:The navigation of Unmanned Aerial Vehicles (UAVs) nowadays is mostly based on Global Navigation Satellite Systems (GNSSs). Drawbacks of satellite-based navigation are failures caused by occlusions or multi-path interferences. Therefore, alternative methods have been developed in recent years. Visual navigation methods such as Visual Odometry (VO) or visual Simultaneous Localization and Mapping (SLAM) aid global navigation solutions by closing trajectory gaps or performing loop closures. However, if th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…One of these is indoor navigation or operation in urban canyon environments where there are many high-rise buildings around the receiver. When there are obstacles blocking the line-of-sight (LOS) signal between the receiver and the user, GNSS signals may have large amounts of multipath due to signals bouncing off structures, which leads to inaccurate ranging measurements, or may be significantly attenuated or unavailable [14]. The second and more troubling limitation is operation in the presence of RFI, such as spoofing or jamming.…”
Section: Gnssmentioning
confidence: 99%
“…One of these is indoor navigation or operation in urban canyon environments where there are many high-rise buildings around the receiver. When there are obstacles blocking the line-of-sight (LOS) signal between the receiver and the user, GNSS signals may have large amounts of multipath due to signals bouncing off structures, which leads to inaccurate ranging measurements, or may be significantly attenuated or unavailable [14]. The second and more troubling limitation is operation in the presence of RFI, such as spoofing or jamming.…”
Section: Gnssmentioning
confidence: 99%
“…Recently, significant results have been achieved by Deep Neural Networks (DNN) in the task of pose estimation based on monocular imagery. In this sense, the use of a Convolutional Neural Network (CNN) [6] to learn and to match features, which aids in camera pose estimation, has become popular with the work of Kendall et al [12] and more recently the work of Mueller et al [30]. However, both approaches rely on prior environmental knowledge before yielding an estimation of the camera position.…”
Section: Related Workmentioning
confidence: 99%
“…It was shown that pose regression in areas with less training data scores worse compared to areas with a dense distribution of training samples (Mueller et al, 2017). Utilizing a photorealistic model for data augmentation showed improvements regarding estimation accuracy (Mueller and Jutzi, 2018). However, photo-realistic models are not as wide distributed or available as triangulated 3D model.…”
Section: Related Workmentioning
confidence: 99%